Determinants and Impact of Corruption on Public Service Delivery in Lafia Local Government Council, Nasarawa State, Nigeria - James Mosimabale Omolaiye (JOURNAL OF POLITICAL SCIENCE AND LEADERSHIP RESEARCH, 2026)
The study examined the determinants and impact of corruption on public service delivery in Lafia, Nasarawa State, Nigeria. Two specific objectives were raised; to identify the determinants of corruption and analyse the impact of corruption on public service delivery in Lafia Local Government. The descriptive survey design was employed and 374 elected officials and senior administrative personnel were selected from 5,933 workers in the council area as sample for the study. A self-structured questionnaire with 21 items and a reliability estimate of 0.06 was used for data collection. The data collected were analysed with descriptive statistics and the results presented in tables. Findings revealed that lack of transparency, weak institutional frameworks, political interference, low salaries of officials, and poor enforcement of anti-corruption laws as responsible for high corruption cases. It was also found that corrupt practices have contributed to delays in service delivery, use of substandard materials in public projects, abandonment of projects, increased costs of services, and inequality in access to services. The study recommended that the government should strengthen institutional services to adopt open governance practices, such as publishing budgets, project costs, and implementation reports for the public to access.